Tourism Law Enforcement in Regional Spatial Planning and Licensing Perspectives - Budiman, Haris; Akhmaddhian, Suwari; Agustin, Dela; Bhandari, Rahul (Unifikasi : Jurnal Ilmu Hukum, 2023)
The development of tourism sector in Kuningan Regency is a reflection of the area's progress and development. Considering licensing and spatial planning perspectives, there was a need to investigate the development of tourism sector in Kuningan Regency. Therefore, this study aimed to analyze tourism licensing mechanisms and tourism law enforcement concerning spatial planning and licensing in Kuningan Regency. A socio-legal method was adopted based on studies of various disciplines, such as tourism, economics, and law. The primary and secondary data used were collected through interviews, observation, and literature study. The result showed that licensing mechanism for tourism development in Kuningan Regency was divided into two categories, namely licensing carried out at the Investment Agency and the One-Stop Integrated Service and the Gunung Ciremai National Park Office. This was because Kuningan Regency had an area included in the National Park zone, directly giving licensing process to the Ministry of Environment and Forestry. Preventive law enforcement efforts were carried out by law enforcement officers, including drafting legal opinions, holding meetings, and avoiding violations during licensing process. In conclusion, the policy and the implementation of law enforcement in licensing and spatial planning for tourism development in Kuningan Regency were carried out well by the regional government and law enforcement officers. However, a renewal of the Kuningan Regency Regional Regulation on a Detailed Spatial Planning as a basis for determining licenses was needed.